Validation of a High-Performance Liquid Chromatographic Method with diod array detection for the Quantification of Flurbiprofen in 100 mg Film-coated Tablet - Nguyen, Thi Thanh Binh; Nguyen, Thanh Hai; Dang, Ngoc Anh; Tran, Mai Anh (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2017)
A high-performance liquid chromatographic method was developed for the quantification of flurbiprofen in 100 mg film-coated tablet in accordance with the direction of the European Medicines Agency and the International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use. 10 µl of flurbiprofen solution was injected onto a C 8 reverse phase column (5 µm, 120 Å, 4.6×150 mm). The mobile phase employed was acetonitrile : water : glacial acetic acid (65 : 32.5 : 2.5, v/v/v) at a flow rate of 1 ml/min. The column effluent was monitored within 8 minutes by diot array detection at 247 nm. The retention time of flurbiprofen was found to be 3.73 minutes. In the concentration range of 2 - 20 μg/ml, there was a tight linear correlation between peak area y (mAU.min) and sample concentration x (μg/ml) according to the equation y = 0,680x as the squared correlation coefficient R 2 was 0.9993. The limit of detection and limite of quantification were respectively 0.05 and 0.15 μg/ml. The method was specific to flurbiprofen with good precision and accuracy. The percentage recovery was ≤ 100 ± 2%, the relative standard deviation of the repeatability was ≤ 1.71% and the relative standard deviation of the intermediate precision was ≤ 2.34%.